Causality Nexus of Foreign Direct Investment and Economic Growth in Tanzania: An Empirical Investigation - Mnaku Honest Maganya (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This paper sought to examine the causality nexus of Foreign Direct Investment (FDI) and Economics Growth in Tanzania. Specifically, the research aim to assess the impact of FDI to manufacturing, agricultural and service sectors. Moreover, the study employed time series data from 1993 to 2023. FDI inflow is always considered an important economic growth catalyst in developing economies. Neoclassical growth theories proposed that FDI enhances economic growth by augmenting capital stock and technology. According to the neoclassical models, FDI does not enhance the long-run growth rate but instead is related to the output level. Autoregressive Distributed Lags (ARDL) models was employed to determine the long-run and causal relationship between variables of interest in all three models of the study. The findings of the manufacturing output model suggest that FDI has positive and statistically significance effect to manufacturing sector in both short run and long run. In agriculture and service sector models only short run estimation was captured due to lack of co-integration pattern among variables. The findings indicated a positive and statistical significant unidirectional causality running from FDI to both agricultural and service sectors output. Based on the findings of the study the policy implication is that Tanzania should emphasize FDI-led growth policies to enhance sustainable economic growth to realize the desired economic objectives at the macro level.